1997
DOI: 10.1086/514094
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides Interfere with the Establishment and Progression of Experimental Pneumococcal Pneumonia

Abstract: Oligosaccharides that block the adherence of bacteria to epithelial cells in vitro--lacto-N-neotetraose (LNnT) and its alpha2-3- and alpha2-6-sialylated derivatives--were tested for their abilities to attenuate the course of pneumococcal pneumonia and to prevent colonization of the nasopharynx in animal models. Intratracheal administration of these agents concurrently with bacteria dramatically decreased pneumococcal load in the lungs of rabbits and conferred protection from bacteremia. The oligosaccharides am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 18 publications
0
75
0
3
Order By: Relevance
“…As for S. pneumoniae, Anderson et al (18) proved in 1986 that lacto-N-tetraose (LNT) and lacto-Nneotetraose (LNnT) can inhibit the adhesion to buccal epithelial cells. The same positive effect of LNnT was also confirmed on lung tumoral cells and animal models (38). On the contrary, Barthelson et al (39), using conjunctival cells, observed a reduced effectiveness of LNnT in inhibiting some Streptococcus strains, while its 6= sialyl-derivative was very effective.…”
Section: Discussionmentioning
confidence: 64%
“…As for S. pneumoniae, Anderson et al (18) proved in 1986 that lacto-N-tetraose (LNT) and lacto-Nneotetraose (LNnT) can inhibit the adhesion to buccal epithelial cells. The same positive effect of LNnT was also confirmed on lung tumoral cells and animal models (38). On the contrary, Barthelson et al (39), using conjunctival cells, observed a reduced effectiveness of LNnT in inhibiting some Streptococcus strains, while its 6= sialyl-derivative was very effective.…”
Section: Discussionmentioning
confidence: 64%
“…For example, P-fimbriated uropathogenic Escherichia coli strains contain an adhesin specific for Galα1-4Gal [19], whereas other E. coli, as well as Klebsiella pneumoniae and Salmonella, produce adhesins that bind to mannose residues [1,[20][21][22][23][24]. In contrast, the gram positive organism, Streptococcus pneumonia, binds carbohydrates containing the linkages Galβ1-3GalNAc and Galβ1-4GluNAc [5,25,26]. The observation that all of these organisms adhere to HEp-2 cells suggests the presence of a diverse array of carbohydrates receptors to which their adhesins are able to bind [20,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This methodological limitation may also be a factor in the finding of similar levels of inflammatory mediators (IL-6, IL-8, and TNF) and markers of lung damage (SP-D, CC-16, and RAGE) in the pulmonary lavage fluid of the two groups [46]. Previous studies have suggested that heparin may inhibit growth of bacteria and viruses in the lungs through limiting their adhesion to respiratory surfaces [20][21][22]. We did not find evidence to support this, and there were similar numbers of new positive bacterial cultures in pulmonary lavage fluid in both groups following enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental models have demonstrated that heparin or other anti-coagulants reduce fibrin deposition in the lungs and improve clinical outcomes [13][14][15][16][17]. Heparin has other actions, including reduced pulmonary edema, reduced leukocyte activation, and inhibition of adhesion of bacteria and viruses to respiratory surfaces, that may also be beneficial [18][19][20][21][22]. Evidence from large, multi-center, clinical studies in patients with severe sepsis also suggests that heparin may improve important clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%